Caribbean Report 17-02-1989 - Patrick Soraya (anchor); Haynes, Desmond (interviewee); Norton, Michael (correspondent); Sanders, Peter (interviewee); Sabri, Sultan (interviewee); Lowe, Chris (correspondent); Patten, Chris (interviewee); Jackson, Colin (interviewee); Rosswess, Michael (interviewee); Edwards, Andy (interviewee) (The British Broadcasting Corporation, 1989)
The National Forum in Haiti is to hand in its recommendations to President Prosper Avril for the establishment of a body to supervise free elections. Correspondent Michael Norton explains that they have to show that democracy is serious in order to obtain the aid that is cut-off by Washington since the aborted election in 1987. The Commission for Racial Equality in Britain is short of money and interviews are conducted with Peter Sanders, Chief Executive at the Commission, Sultan Sabri, civil servant, and Chris Patten, the Home Office Minister. In sports, West Indies opening batsman Desmond Haynes is to sign a contract to play for Middlesex and interviews are held with British athletes with connections in Jamaica, Colin Jackson and Michael Rosswess on the forthcoming European Indoor Championships in Hague. The Report also looks at a review of Caribbean News in the British Press during the past week.
1. Headlines (00:00-00:40)
2. The National Forum in Haiti is to hand in its recommendations to the President for the establishment of a body to supervise free elections (00:41-02:50)
3. The Commision for Racial Equality in Britain is short of money. Interviews with Peter Sanders, Chief Executive at the Commission, Sultan Sabri, civil servant, and Chris Patten, Home Office Minister (02:51-05:20
4. Financial News (05:21-06:18)
Keywords: Elections -- Haiti.; Race relations.; Ethnic relations.; Cricket -- Caribbean Area.; Sports -- Caribbean Area.; Track and field -- Great Britain.; Caribbean Area -- Press coverage.; Great Britain -- Press Coverage -- Caribbean Area.; Avril, Prosper.; Commission for Racial Equality.